Sarcoma of the Uterus. Guideline of the DGGG and OEGGG (S2k Level, AWMF Register Number 015/074, February 2019) - Denschlag, Dominik; Ackermann, Sven; Battista, Marco Johannes; Cremer, Wolfgang; Egerer, Gerlinde; Follmann, Markus; Haas, Heidemarie; Harter, Philipp; Hettmer, Simone; Horn, Lars-Christian; Juhasz-Boess, Ingolf; Kast, Karin; Köhler, Günter; Kröncke, Thomas; Lindel, Katja; Mallmann, Peter; Meyer-Steinacker, Regine; Mustea, Alexander; Petru, Edgar; Reichardt, Peter; Schmidt, Dietmar; Strauss, Hans-Georg; Tempfer, Clemens; Thiel, Falk; Ulrich, Uwe; Vogl, Thomas; Vordermark, Dirk; Gass, Paul; Beckmann, Matthias W. (Geburtshilfe und Frauenheilkunde, 2019)
Aims This is an official guideline published and coordinated by the German Society of Gynecology and Obstetrics (DGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). Because of their rarity and heterogeneous histopathology, uterine sarcomas are challenging in terms of how they should be managed clinically, and treatment requires a multidisciplinary approach. To our knowledge, there are currently no binding evidence-based recommendations for the appropriate management of this heterogeneous group of tumors.Methods This S2k guideline was first published in 2015. The update published here is the result of the consensus of a representative interdisciplinary group of experts who carried out a systematic search of the literature on uterine sarcomas in the context of the guidelines program of the DGGG, OEGGG and SGGG. Members of the participating professional societies achieved a formal consensus after a moderated structured consensus process.Recommendations The consensus-based recommendations and statements include the epidemiology, classification, staging, symptoms, general diagnostic work-up and general pathology of uterine sarcomas as well as the genetic predisposition to develop uterine sarcomas. Also included are statements on the management of leiomyosarcomas, (low and high-grade) endometrial stromal sarcomas and undifferentiated uterine sarcomas and adenosarcomas. Finally, the guideline considers the follow-up and morcellation of uterine sarcomas and the information provided to patients.Ziel Offizielle Leitlinie, publiziert und koordiniert von der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) und der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG). Aufgrund ihrer Seltenheit und heterogenen Histopathologie stellen uterine Sarkome eine Herausforderung bez. des klinischen Managements dar und bedürfen von daher eines multidisziplinären Ansatzes. Nach unserem Kenntnisstand existieren bis dato keine verbindlichen, evidenzbasierten Empfehlungen bez. des angemessenen Managements dieser heterogenen Tumoren.Methoden Die vorliegende S2k-Leitlinie wurde erstmals 2015 publiziert. Das nun hier publizierte Update ist erneut das Ergebnis eines Konsenses eines repräsentativen interdisziplinären Expertenkomitees, das im Rahmen des Leitlinienprogramms der DGGG, OEGGG und SGGG eine systematische Literaturrecherche zum Thema uterine Sarkome durchgeführt hat. Mitglieder der beteiligten Fachgesellschaften entwickelten in einem strukturierten Prozess einen moderierten formalen Konsensus.Empfehlungen Die konsentierten Empfehlungen und Statements beziehen sich auf die Epidemiologie, Klassifikation, Stadieneinteilung, Symptomatik, allgemeine Diagnostik, allgemeine Pathologie bzw. genetische Prädisposition von uterinen Sarkomen. Weiterhin werden Aussagen über das Management von Leiomyosarkomen, endometrialen Stromasarkomen (low- und high-grade) und undifferenzierten uterinen Sarkomen und Adenosarkomen getroffen. Abschließend werden die Nachsorge, das Morcellement und die Patientinnenaufklärung von bzw. bei uterinen Sarkomen erwähnt.
Keywords: uterine sarcoma; leiomyosarcoma; endometrial stromal sarcoma; adenosarcoma; morcellation